Assessment of face validity of a disease model of nonsense mutation Duchenne muscular dystrophy: a multi-national Delphi panel study. (31st December 2022) - Landfeldt, Erik; Zhang, Rongrong; Childs, Anne-Marie; Johannsen, Jessika; O'Rourke, Declan; Sejersen, Thomas; Strautmanis, Jurgis; Schara-Schmidt, Ulrike; Tulinius, Mar; Walter, Maggie C.; Willis, Tracey; Buesch, Katharina
Abstract: Objective: The objective of this study was to assess the face validity of a disease model evaluating the cost-effectiveness of ataluren for the treatment of nonsense mutation Duchenne muscular dystrophy (nmDMD). Methods: This was a Delphi panel study comprising of physicians with first-hand experience of ataluren for the treatment of nmDMD. Consensus was sought for previously unvalidated model data, including patient health status and quality of life measured using the Health Utility Index (HUI), mortality, informal caregiving, and the expected benefit of early ataluren treatment across four states: (1) ambulatory, (2) non-ambulatory, not yet requiring ventilation support, (3) non-ambulatory, night-time ventilation support, and (4) non-ambulatory, full-time ventilation support. Results: Nine experts from five countries participated in the Delphi panel. Consensus was obtained for all questions after three panel rounds (except for two HUI-questions concerning hand function [dexterity]). Consensus HUI-derived utilities for state (1) were 1.0000 for ataluren on top of best supportive care (BSC) and 0.7337 for BSC alone. Corresponding estimates for state (2) were 0.3179 and 0.2672, for state (3) 0.1643 and 0.0913, and for state (4) −0.0732 and −0.1163. Consensus mortality rates for states (1), (2), and (3) were 4%, 13%, and 33%, and life expectancy in state (4) was agreed to be 3 years. Panelists further agreed that two informal caregivers typically provide day-to-day care/support to patients with nmDMD, and that starting treatment with ataluren at 2 versus 5 years of age would be expected to delay loss of ambulation by an additional 2 years, and initiation of night-time and full-time ventilation support by an additional 3 years, respectively. Limitations: The main limitation concerns the size of the Delphi panel, govern primarily by the rarity of the disease. Conclusion: This study confirms the face validity of key clinical parameters and assumptions underlying the ataluren cost-effectiveness model.